Sequences that regulate the divergent GAL1-GAL10 promoter in Saccharomyces cerevisiae. - Johnston, M (1984)
The GAL1 and GAL10 genes of Saccharomyces cerevisiae are divergently transcribed, with 606 base pairs of DNA separating their transcription initiation sites. These two genes are stringently coregulated: their expression is induced ca. 1,000-fold in cells growing on galactose and is repressed by growth on glucose. The nucleotide sequence of the region of DNA between these genes and the precise sites of transcription initiation are presented here. The most notable feature of the nucleotide sequence of this region is a 108-base-pair guanine-plus-cytosine-rich stretch of DNA located approximately in the middle of the region between GAL1 and GAL10. Analysis of the effects of mutations that alter the region between these two genes, constructed in vitro or selected in vivo, suggest that these guanine-plus-cytosine-rich sequences are required for the expression of both genes. The region of DNA between GAL1 and GAL10 is sufficient for regulation of expression of these genes: fusion of the region to the yeast HIS3 gene places HIS3 under GAL control.